Metabolic syndrome and physical activity in southern Brazilian community-dwelling elders: a population-based, cross-sectional study - Reichert César L; Dalacorte Roberta R; Vieira José L (BMC, 2009)
Abstract Background - The association between a sedentary lifestyle and obesity is well documented, and is linked to an increased prevalence of metabolic syndrome (MS). There is some evidence that information regarding the health benefits of physical activity is beginning to impact on the elderly people and is beginning to change their behavior. We aimed to investigate the level of physical activity undertaken by elderly people with MS and those without this condition. Methods - We evaluated 362 community-dwelling elders of Novo Hamburgo, southern Brazil. Diagnosis of MS was based on the International Diabetes Federation criteria and the physical activity (PA) level was estimated by the International Physical Activity Questionnaire. Analysis of covariance was carried out to verify associations between MS risk factors and the level of PA. Logistic regression was used to estimate the MS odds ratio for each level of PA. Results - No significant association was found between MS and the level of physical activity, irrespective of sex. The odds ratio for the presence of MS adjusted for sex and age and using insufficiently active elderly people as reference was 1.04 (95% CI, 0.6 to 1.7) in sufficiently active elderly people and 1.15 (95% CI, 0.7 to 2.0) in very active elderly people. Conclusion - The elderly citizens of a southern Brazilian community who were diagnosed with MS presented the same levels of PA as the individuals who did not have this diagnosis. This may imply that information on the importance of physical activity has already reached this higher risk population.